(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
The study investigated educational management and supervision innovations for achieving educational goals in public secondary schools in Awka North Local Government Area, Anambra. The study adopted a descriptive survey research design. The population of 155 teachers from 8 public secondary schools in Awka North Local Government Area of Anambra State was used. Structured questionnaire titled “Education Management and Supervision Innovation Questionnaire (EMISQ)” was used to collect data. Three experts validated the instruments all from faculty of Education, Unizik Awka. The instrument reliability was tested using Cronbach Alpha Cofficients and it obtained coefficient value of 0.82 indicating that it is reliable for the study. Data were analysed using mean scores. The study revealed that there are ICT innovations, management and supervision in education management for achieving educational goals in public secondary schools in Awka North Local Government Area of Anambra State. Based on the findings, it was recommended among others that government and educational stakeholders should encourage the adoption of ICT in education management in public secondary schools in Awka North Local Government Area.